2005
DOI: 10.1037/0278-7393.31.3.568
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Word Frequency and Similarity on Recognition Judgments: The Role of Recollection.

Abstract: K. J. Malmberg, J. Holden, and R. M. reported more false alarms for low-than highfrequency words when the foils were similar to the targets. According to the source of activation confusion (SAC) model of memory, that pattern is based on recollection of an underspecified episodic trace rather than the error-prone familiarity process. The authors tested the SAC account by varying whether participants were warned about the nature of similar foils and whether the recognition test required the discrimination. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 43 publications
(61 reference statements)
1
11
0
Order By: Relevance
“…The familiarity of reversed-plurality lures should be very similar to the familiarity of the study item, thus requiring recollection of the study event to determine the exact form of the word that was seen previously. This assumption is supported by the finding that there are more know responses to similar foils than to target items in a reversed-plurality task (Park et al, 2005). 9 Also, ERP evidence shows that the FN400, which reflects brain activity that is thought to be a correlate of familiarity-based processing, does not distinguish between old items and reversed-plurality items, indicating that familiarity is the same for both types of items (Curran, 2000;Curran & Cleary, 2003).…”
Section: Remembersupporting
confidence: 56%
See 3 more Smart Citations
“…The familiarity of reversed-plurality lures should be very similar to the familiarity of the study item, thus requiring recollection of the study event to determine the exact form of the word that was seen previously. This assumption is supported by the finding that there are more know responses to similar foils than to target items in a reversed-plurality task (Park et al, 2005). 9 Also, ERP evidence shows that the FN400, which reflects brain activity that is thought to be a correlate of familiarity-based processing, does not distinguish between old items and reversed-plurality items, indicating that familiarity is the same for both types of items (Curran, 2000;Curran & Cleary, 2003).…”
Section: Remembersupporting
confidence: 56%
“…The SAC model has also been described in previously published articles (Cary & Reder, 2003;Park, Reder, & Dickison, 2005;Reder et al, 2000;Schunn, Reder, Nhouyvanisvong, Richards, & Stroffolino, 1997). Whenever further details or model complexities are necessary to explain a set of results, these will be noted in the description of the specific implementation.…”
Section: The Sac Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Malmberg showed that this solution has much to recommend it, but he also noted that one-process models have been formulated and evaluated for both associative recognition (e.g., Wixted, 2007) and plurality discrimination (e.g., McClelland & Chappell, 1998; Park, Reder, & Dickison, 2005). Although Malmberg pointed out that some of these models make unrealistic assumptions about levels of overlap between targets and distractors, their existence means that the controversy over recognition-based measurement is unlikely to abate by switching to associative recognition and plurality discrimination.…”
mentioning
confidence: 99%